Roles of DNA helicases and Exo1 in the avoidance of mutations induced by Top1-mediated cleavage at ribonucleotides in DNA - Niu, Hengyao; Potenski, Catherine J.; Epshtein, Anastasiya; Sung, Patrick; Klein, Hannah L. (Cell cycle (Georgetown, Tex.), 2016)
The replicative DNA polymerases insert ribonucleotides into DNA at a frequency of approximately 1/6500 nucleotides replicated. The rNMP residues make the DNA backbone more susceptible to hydrolysis and can also distort the helix, impeding the transcription and replication machineries. rNMPs in DNA are efficiently removed by RNaseH2 by a process called ribonucleotides excision repair (RER). In the absence of functional RNaseH2, rNMPs are subject to cleavage by Topoisomerase I, followed by further processing to result in deletion mutations due to slippage in simple DNA repeats. The topoisomerase I-mediated cleavage at rNMPs results in DNA ends that cannot be ligated by DNA ligase I, a 5′OH end and a 2′-3′ cyclic phosphate end. In the budding yeast, the mutation level in RNaseH2 deficient cells is kept low via the action of the Srs2 helicase and the Exo1 nuclease, which collaborate to process the Top1-induced nick with subsequent non-mutagenic gap filling. We have surveyed other helicases and nucleases for a possible role in reducing mutagenesis at Top1 nicks at rNMPs and have uncovered a novel role for the RecQ family helicase Sgs1 in this process.